(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article is devoted to the problem of the formation of positive motivation in people with the status of an orphan (child deprived of parental care). The specificity of the terms of becoming the personality of orphans is emphasized as a circumstance for varying the motivational sphere of the subjects. The results of an empirical study of the orientation of the educational motivation of people with the corresponding status are presented, based on the dominance of one of the motives — achieving success or avoiding (fear) failure in educational and professional activities. The results obtained are compared with the indicators of subjects who were brought up in parental families. The conclusion is drawn about the general trend of the dominance of positive educational motivation among subjects, including orphans.